(untitled) (CIPEEX, 2025)
The use of estrous cycle suppressors, commonly known as "anti-estrus vaccines," relies on medroxyprogesterone, a synthetic analog of progesterone, as its active ingredient. Its contraceptive mechanism works by suppressing the frequency of gonadotropin-releasing hormone (GnRH) pulses and reducing the release of luteinizing hormone (LH) and follicle-stimulating hormone (FSH), which are essential for follicular maturation and ovulation. Although hormonal therapy is indicated in specific cases, its routine use should be avoided due to the severe adverse effects it can cause. Bill No. 4853/2020 proposes the prohibition of the use and commercialization of "anti-estrus" medications without veterinary prescription due to the associated risks. In contrast, Law No. 13.426/2017 establishes permanent sterilization as a legal strategy for the population control of dogs and cats, holding municipalities accountable for implementing and promoting responsible pet ownership. Despite the known risks, many pet owners use it for prolonged periods to suppress the estrous cycle, prevent reproduction, or terminate pregnancies, leading to severe complications that may compromise the reproductive system and, in extreme cases, result in death. This case report presents a female Jack Russell Terrier named Teisse, who was brought to the UniEvangélica Veterinary Clinic on August 19, 2024. During the anamnesis, the owner reported that the dog had not been spayed, had undergone two pregnancies, and had received doses of the "anti-estrus vaccine." The owner sought veterinary care due to the presence of recurring mammary tumors in the caudal thoracic mammary gland, resembling the size of a coin, and a larger ulcerated mass in the cranial abdominal mammary gland. Previously, the patient had undergone unilateral total mastectomy on the left side. On September 12, 2024, nodulectomy surgery was performed to remove the two ulcerated masses, which were sent for histopathological examination. Regarding the results of complementary tests, the patient presented with normocytic anemia in the erythrogram, lymphopenia, and a left shift in the leukogram. However, ultrasonographic and X-ray examinations did not reveal significant alterations. Biochemical parameters, including ALT, creatinine, urea, and AST, were within the reference ranges for the species. It is evident that the use of contraceptives is an accessible and lower-cost alternative but predisposes female dogs to the development of mammary neoplasms, uterine alterations such as pyometra and endometritis, metabolic disorders such as diabetes mellitus, and can also lead to fetal alteration and maceration, putting both the mother and offspring at risk. It is concluded that surgical sterilization, such as ovariohysterectomy (spaying), is superior, effective, and safer, as it does not cause adverse effects and harm to animal health compared to the "anti-estrus vaccine," thereby promoting better quality of life and preventing adverse effects in companion animals.